The Impact of Income Diversification and Liquidity Risk on Stability of Conventional Banks In Indonesia - Abi Gustama; Dwi Nastiti Danarsari (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the effect of income diversification and liquidity risk on the stability of conventional banks in Indonesia, the research of banks listed on Indonesia Stock Exchange during the periode 2014 – 2023 and using panel data regression methods. The results indicate that income diversification has a significant negative effect on bank stability. However, the moderating factors of KBMI 3 and KBMI 4 are able to strengthen the relationship between income diversification and bank stability. Liquidity risk doest not affect bank stability, While KBMI 1 and KBMI 4 are found waken the impact of liquidity risk on stability. In Contrast KBMI 2 strengthen effect of liquidity risk on bank stability. Banks need to carefully consider banking activities in diversifying income an take into account tier capital 1 in mitigating liquidity risk. KBMI as a moderating both income diversification and liquidity risk. To the best of the author's knowledge, KBMI as a moderating variable in the relationship between income diversification and liquidity risk has not been previously examined. The implication of this study highlights the importance of regulatory oversight regarding risk exposure arising from income diversification and the optimization of liquidity within each KBMI category.